Spatial learning and memory deficits induced by prenatal glucocorticoid exposure depend on hippocampal CRHR1 and CXCL5 signaling in rats - Zheng, You (J Neuroinflammation, 2021)
BACKGROUND: Prenatal synthetic glucocorticoid (sGC) exposure increases the susceptibility to cognitive and affective disorders in postnatal life. We previously demonstrated that prenatal sGC exposure results in an increase in corticotropin-releasing hormone (CRH) receptor type 1 (CRHR1) expression in the hippocampus of rats, and CRHR1 is involved in synapse formation via regulation of C-X-C chemokine ligand 5 (CXCL5) in hippocampus. We sought to investigate that the roles of CRHR1 and CXCL5 in learning and memory impairment caused by prenatal sGC exposure. METHODS: Pregnant rats were administered with saline or dexamethasone (DEX) from gestational day (GD) 14 to GD21. DEX offspring at 2-day old were treated with saline and CRHR1 antagonists (antalarmin and CP154526) for 7 days. Some DEX offspring received intra-hippocampal injection of AAV9 carrying CXCL5 gene. Spatial learning and memory was assessed by Morris water maze test. Immunofluorescence analysis was applied to show synapsin I and PSD95 signals in hippocampus. Synapsin I and PSD95 protein level and CXCL5 concentration were determined by western blotting and ELISA, respectively. Organotypic hippocampal slice cultures were used to investigate the effect of DEX on CXCL5 production in vitro. RESULTS: Both male and female DEX offspring displayed impairment of spatial learning and memory in adulthood. Synapsin I and PSD95 signals and CXCL5 levels were decreased in DEX offspring. DEX offspring with antalarmin and CP154526 treatment showed improved spatial learning and memory. Antalarmin and CP154526 treatment increased synapsin I and PSD95 signals and CXCL5 concentration in hippocampus. Bilaterally hippocampal injection of AAV9 carrying CXCL5 gene improved the spatial learning and memory and increased CXCL5 concentration and synapsin I and PSD95 levels in hippocampus. DEX dose-dependently suppressed CXCL5 production in cultured hippocammpal slices, which was prevented by antalarmin treatment. CONCLUSION: CRHR1 and CXCL5 signaling in the hippocampus are involved in spatial learning and memory deficits caused by prenatal DEX exposure. CRHR1 activation contributes to decreased CXCL5 production in hippocampus induced by prenatal DEX treatment. Our study provides a molecular basis of prenatal GC exposure programming spatial learning and memory.